The Institutionalisation of Sami Interest in Municipal Comprehensive Planning: A Comparison Between Norway and Sweden - Bjärstig, Therese; Nygaard, Vigdis; Riseth , Jan Åge; Sandström , Camilla (International Indigenous Policy Journal, 2020)
The Sami are recognized as an Indigenous people and a national minority in both Norway and Sweden, and their involvement in any planning concerning their traditional territories is required. The aim of this article is to examine how Sami interests are secured and institutionalized in municipal comprehensive planning (MCP). We use two case study areas: Sortland municipality in Norway and Vilhelmina municipality in Sweden. Analysis of various qualitative materials indicates that, despite contextual and institutional differences, the planning processes in the case study areas have similar outcomes. We conclude that formal rights of the Sami are not always acknowledged by the politicians who make the final decision. Rather, the Sami depend on the politicians’ willingness to consider their needs.